Una storia di fantasia. Sul metodo storico-filosofico di Husserl e sulla storicità produttiva - Biagini, Lorenzo (Bollettino Filosofico, 2024)
This article focuses on Husserl’s historical-philosophical method as outlined in The Crisis of European Sciences. My main goal is to understand why in his view philosophical historicity can be considered productive. I will first address Husserl’s idea of historical-teleological reflection emphasizing the existential and linguistic dimension of the phenomenological Rückfrage. I will then develop these aspects by referring to the way Adorno interprets the connection between history, terminology, and phantasy. Finally, Ricoeur’s analyses of productive imagination will clarify how the philosopher can construct the teleological and dialectical unity of history as a “philosophical poem”. These steps will allow to conclude that philosophical historicity is artistic and scientific at the same time, and that it is productive insofar as it is founded on the generative power of imagination. Keywords: Husserl, Motivation, Productive Historicity, Productive Imagination, Teleology